Privacy concerns arising from internet service personalization filters - Koene, Ansgar; Perez, Elvira; Carter, Christopher J.; Statache, Ramona; Adolphs, Svenja; O’Malley, Claire; Rodden, Tom; McAuley, Derek (Association for Computing Machinery (ACM), 2015)
Personal service customization, or personalization, is one of the core tools that are being used by on-line providers of information services such as search engines, social media, news sites and product recommender systems to optimize the individual user experience in hopes of attracting and keeping users. In this paper we will examine the user profile models that are used to achieve this information personalization. From a citizen centric perspective, our concerns focus on the degree of privacy intrusion that is implicitly required to determine the parameter settings of the information filter profile and the ethical implications of the personal behavior predicting properties of the user model itself.